Education through a new window including diversity and students background in EFL teaching - Soto, Sandy T. (2015)
Education is the future of the countries. If a country wants to grow and improve the living conditions of its citizens, it is important to start building strong foundations. The foundations are the children and the youth that are currently studying to somehow contribute with the country development. We, as teachers, have the big responsibility of forming children and educate the future professionals of our country. That responsibility demands a good preparation and constant reflection on our practices as educators. Constantly, we have to ask ourselves: am I doing a good job? Am I constantly improving my knowledge to become a better person and professional? If so, how can I demonstrate that I am reflecting and growing in my field of work? In this book, we include scientific and empirical knowledge gained through a journey that started when we decided to become educators. We will discuss some important concepts about education, and the ways how we have applied those concepts while teaching English as a Foreign Language. The implementation of new educational standards and the importance of speaking English in the modern society demands that students be able to communicate and access to academic information in English. Thus, English teachers have to be well-prepared to perform successfully our job as English teachers. It means that we have to know the approaches, methods, and techniques that allow students to acquire or learn a new language. Moreover, taking into consideration that students not only need English to communicate, but also for academic purposes, teachers have to find the way how to teach English and academic content together. We have to teach a foreign language to a cultural and linguistically diverse group of students each year. Thus, we have to know the ways to utilize that diversity as an asset and as a bridge to motivate students and engage them in the learning process. Being diverse is not necessarily being from other ethnicity or other language. Students have different in skills, likes, interests, and ways of learning things. Taking this into consideration, it does not make sense to apply a single teaching method or evaluation to such diverse students.